KINETICS OF MICROBIAL SULFATE REDUCTION IN ESTUARINE SEDIMENTS - Pallud C.; Van Cappellen P. (My University, 2006)
Kinetic parameters of microbial sulfate reduction in intertidal sediments from a freshwater, brackish and marine site of the Scheldt estuary (Belgium, the Netherlands) were determined. Sulfate reduction rates (SRR) were measured at 10, 21, and 30 °C, using both flow-through reactors containing intact sediment slices and conventional sediment slurries. At the three sites, and for all depth intervals studied (0-2, 2-4, 4-6 and 6-8 cm), the dependence of potential SRR on the sulfate concentration followed the Michaelis-Menten rate equation. Apparent sulfate half-saturation concentrations, Km, measured in the flow-through reactor experiments were comparable at the freshwater and marine sites (0.1-0.3 mM), but somewhat higher at the brackish site (0.4-0.9 mM). Maximum potential SRR, Rmax, in the 0-4 cm depth interval of the freshwater sediments were similar to those in the 0-6 cm interval of the marine sediments (10-46 nmol cm-3 h-1 at 21 °C), despite much lower in situ sulfate availability and order-of-magnitude lower densities of sulfate-reducing bacteria (SRB), at the freshwater site. Values of Rmax in the brackish sediments were lower (3.7-7.6 nmol cm-3 h-1 at 21 °C), probably due to less labile organic matter, as inferred from higher Corg/N ratios. Inflow solutions supplemented with lactate enhanced potential SRR at all three sites. Slurry incubations systematically yielded higher Rmax values than flow-through reactor experiments for the freshwater and brackish sediments, but similar values for the marine sediments. Transport limitation of potential SRR at the freshwater and brackish sites may be related to the lower sediment porosities and SRB densities compared to the marine site. Multiple rate controls, including sulfate availability, organic matter quality, temperature, and SRB abundance, modulate in situ sulfate-reducing activity along the estuarine salinity gradient. ? 2005 Elsevier Inc. All rights reserved.
Keywords: ESTUARINE SEDIMENT; REACTION KINETICS; SEDIMENT CHEMISTRY; SULFATE-REDUCING BACTERIUM